INNOVATIVE MARKETING STRATEGIES FOR PUBLIC LIBRARIES IN THE AGE OF DIGITAL TRANSFORMATION - Metwally, Ahmed Sayed M.; Alotaibi, Faiz A.; Alzahrani, Saad; Abdelati, Mohamed H. (Veredas do Direito, 2025)
Within the traditional era, public libraries were used to gain knowledge and enhance the user's intellect and access to books. In the digital era, these libraries have lost their true essence. However, social media strategies have aimed to revive and maintain the influence of public libraries on diverse communities. Hence, the current research aims to investigate public libraries' marketing strategies in the digital era. The research adopted a mixed-method research design, conducted from January 2023 to December 2023, to implement quantitative and qualitative assessments, including 650 participants selected through purposive sampling, to assess the individuals' perspectives on implementing marketing strategies in public libraries within the digital era. Moreover, the research conducted eight in-depth interviews with 20 library professionals to accentuate the perceptions, attitudes, and experiences of library professionals when implementing marketing strategies in public libraries within the digital era. Case studies on specific libraries were conducted to assess the importance of social media and the digital presence of libraries. The research findings manifest. Public libraries should develop innovative strategies to maximize their marketing potential in the digital era. However, such advancements and efficiencies in using social media platforms will provide a better online reputation for public libraries while replenishing their need within the community.